2001
DOI: 10.1093/occmed/51.5.347
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sickness absence--risk indicators among occupationally active residents of a Danish county

Abstract: This study aims to identify risk factors and their prevalence in long-term sickness absence. The study is designed as a case-referent study which comprises 481 participants who have experienced a sickness absence lasting >10 weeks and a reference group of 1326 individuals in active employment. Multivariate analysis identified the following significant risk factors for men: (i) age >50 years [odds ratio (OR) = 2.4]; (ii) short period of education (OR = 2.3); (iii) unemployment within the last 3 years (OR = 1.7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 11 publications
(15 reference statements)
2
28
2
Order By: Relevance
“…We cannot exclude that a more elaborate assessment of work-related factors may lead to different results. A low educational level proved to be predictive of long-term sickness absence in a cohort of Danish employees (22). Surprisingly, we found that a high level of education was predictive of a longer time to return to work.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…We cannot exclude that a more elaborate assessment of work-related factors may lead to different results. A low educational level proved to be predictive of long-term sickness absence in a cohort of Danish employees (22). Surprisingly, we found that a high level of education was predictive of a longer time to return to work.…”
Section: Discussioncontrasting
confidence: 72%
“…Being a female increased the likelihood of return to work in two studies (8,21), while it decreased this likelihood in another study (10). Older age was predictive of not returning to work (10,13,(17)(18)(21)(22). Being divorced also decreased the likelihood of return to work (10).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies point toward an association between perceived psychosocial work conditions and sickness absence (17,25,(33)(34)(35). It can be speculated that a general negative social climate makes employees more prone to report higher physical exertion or that psychosocial work factors per se are associated with sickness absence.…”
Section: Discussionmentioning
confidence: 99%